2022
DOI: 10.1097/mao.0000000000003518
|View full text |Cite
|
Sign up to set email alerts
|

Enlarged Vestibular Aqueduct: Disease Characterization and Exploration of Potential Prognostic Factors for Cochlear Implantation

Abstract: Objectives:There is an unmet need to match the anticipated natural history of hearing loss (HL) in enlarged vestibular aqueduct (EVA) with clinical management strategies. The objectives of this study are therefore to provide a detailed case characterization of an EVA cohort and explore the relationship between candidate prognostic factors and timing of cochlear implant (CI) surgery.Study Design:A multicenter retrospective review of patients diagnosed with EVA.Setting:Patient data recruitment across three CI ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
1
4
0
Order By: Relevance
“…In other words, before a child with a mutation enters kindergarten, they may have a hearing loss that has progressed sufficiently to warrant conversations and referrals for implantation, but not as many would enter these conversations without a known mutation. Our results are consistent with reports of EVA and monitoring for cochlear implant candidacy in a large cohort study recently conducted in the United Kingdom (Saeed et al 2022). Their study found that EVA patients often qualified as cochlear implant candidates in at least one ear by the age of three years.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In other words, before a child with a mutation enters kindergarten, they may have a hearing loss that has progressed sufficiently to warrant conversations and referrals for implantation, but not as many would enter these conversations without a known mutation. Our results are consistent with reports of EVA and monitoring for cochlear implant candidacy in a large cohort study recently conducted in the United Kingdom (Saeed et al 2022). Their study found that EVA patients often qualified as cochlear implant candidates in at least one ear by the age of three years.…”
Section: Discussionsupporting
confidence: 93%
“…Being proactive is challenging because outcomes are variable, and we know that progression may occur but not when or by how much. Thus, there is an unmet need to improve our understanding of EVA by exploring potential clinical prognostic factors for hearing loss severity and progression (Saeed et al 2022). Understanding the implications of their hearing loss is crucially important as they progress through social and communication developmental periods.…”
Section: Introductionmentioning
confidence: 99%
“…This is contrary to previous low risk of bias studies but may be explained by the fact different outcome measures have been used between studies, and an interplay between multiple factors determines timeframes for CI surgery. 3 , 9 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…We did not categorize variants by a number of mutated alleles as our previous work failed to show an association with HL and conflicting associations are reported in the literature. 3 , 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation